Phytochemistry of plants from genus phyllanthus - Kumar, Brijesh; Madhusudanan, K. P.; Kumar, Sunil (Boca Raton : CRC Press, 2020)
Several Phyllanthus species are widely used in traditional medicine and herbal formulation for the treatment of a variety of ailments such as flu, dropsy, diabetes, jaundice and bladder calculus. The medicinal properties of these species are due to the presence of lignans, flavonoids, tannins, alkaloids and terpenoids. Phyllanthin and hypophyllanthin are the major lignans from Phyllanthus species having estrogenic properties that reduce toxicity and vascular tension, and protect hepatocytes. This book deals with the importance of separation techniques in screening of major lignans, flavonoids and terpenoids in Phyllanthus species using HPLC/UPLC coupled with mass spectrometric techniques. Features: Collection of Ayurvedic features and scientific evidence of important medicinal plants. Screening of major lignans, flavonoids and terpenoids in plant parts/whole plant extracts and their geographical variations in Phyllanthus amarus. Easy-to-use analytical procedure for the quality control of Phyllanthus and its products.
OCLC-licensed vendor bibliographic record.
Keywords: Phyllanthus; Botanical chemistry; MEDICAL / Pharmacology; SCIENCE / Chemistry / General